HISTORICAL ASPECTS OF FORMATION AMERICAN LEGAL SYSTEM - Пильгун, Наталія Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
The purpose: this article deals with the historical aspect of the formation of the American legal system, the functioning of American common law and its sources. It is proved that the legal precedent occupies a central place in the legal system of the Anglo-Saxon direction. Methods of the research: historical method, comparative-legal method. Results: it is determined that the peculiarities of American legal system lie in the source of law, its structure and application. Discussion: of the historical aspect of formation of American legal system in the system of American common law.